Tenocytes form a 3‐D network and are connected via nanotubes. Issue 1 (30th September 2019) - Egerbacher, Monika; Gabner, Simone; Battisti, Sarah; Handschuh, Stephan
Abstract: Cells use different cell adhesion and communication structures to promote tissue development, maintenance of tissue integrity as well as repair and regenerative processes. Another recently discovered way of information exchange is long‐distance thin cellular processes called nanotubes (NTs), mainly studied in vitro . Information on the existence and relevance of NTs in vivo is sparse. Building on two references which hint at the potential existence of longitudinally directed cell processes resembling NTs, we investigated tendons from young (3 weeks) and adult (9 weeks, 4 and 8 months) Fisher rats. Whole mounts of rat tail tendon fascicles (RTTfs) and sections of Achilles, flexor, extensor and patellar tendons were stained with Deep Red plasma membrane and DAPI nuclear stain and immunolabelled with Connexin43 (Cx43). In addition, 3‐D reconstruction of serial semithin sections and TEM was used to verify the presence of NTs. We were able to demonstrate NTs as straight thin longitudinal processes (Ø 100–500 nm) reaching up to several 100 μm in length, mainly originating from lateral sheet‐like cell processes or cell bodies in all tendon types investigated. NTs were observed to distend between tenocyte rows at the same level but also connect cells of different rows, thus leading to a complex 3‐D cellular scaffold. Shorter NTs connected lateral cell sheets of tenocytes in the same row, omitting one or two cells. In addition, we detected links or potential branching of NTs. Cx43 immunostaining for the detection of gap junctions revealed Cx43‐positive foci at the end‐to‐end contacts of tenocyte cell bodies as well as along their contacting sheet‐like processes. Only rarely, we found clear Cx43 signals at their potential contact points between NTs and tendon cells as well as along the course of NTs, and most NTs appeared completely devoid of Cx43 signals. Therefore, we conclude that NTs in tendons could have a twofold function: long‐distance communication as well as stabilization of a mechanically challenged tissue. From in vitro studies it is known that NTs allow intercellular transmission of various cell components, offering potential protective effects for the respective tissue. Further studies on functional properties of NTs in tendons under changing mechanical loading regimens are required in the future. The fact that NTs are present in tendons may necessitate the reconsideration of our traditional understanding of cell‐to‐cell communication. Abstract : Nanotubes (NTs), a recently discovered way of information exchange comprising long‐distance thin cellular processes, are present in tendons. Together with the well‐known flat sheet‐like lateral processes, NTs form a complex three‐dimensional cellular network. NTs in tendons could have a twofold function: long‐distance communication as well as stabilization of a mechanically challenged tissue, and may require the reconsideration of our traditional understanding of cell‐to‐cell communication.